Pragmatic Competence: how can it be developed in the foreign language classroom? - Aquino, Carla de (BELT - Brazilian English Language Teaching Journal, 2012)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>This paper aims at bringing into account the possibility of developing pragmatic competence with students in the foreign language classroom. It also considers features of the task-based approach, a method of language teaching, which would enable pragmatic awareness raise. It suggests that it is possible to give a pragmatic focus to language learning through task-based materials in order to help learners develop culture-specific pragmatic features, due to common aspects between pragmatic competence development and methodology based on tasks.